2019
DOI: 10.1590/1984-70332019v19n1a01
|View full text |Cite
|
Sign up to set email alerts
|

Effective population size and genetic gain expected in a population of Coffea canephora

Abstract: This work aimed to study the effective population size and genetic gain in a population of robusta coffee (Coffea canephora Pierre) and verify the possibility of using recurrent selection. The experiment comprised 25 treatments, consisting of 21 C. canephora progenies and four C. arabica (cultivars) grown in Brazil. The experimental design was a 5x5 quadruple balanced lattice, with 24 replications, with one plant per plot. Six harvests were performed in each plant. Statistical analysis was carried out using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Except for the trait canopy diameter, the genotypic effects were significant ( Table 4 ), indicating the existence of genetic variability among clones. Mistro et al [ 20 ], evaluating conilon coffee progenies for yield per plant, also found genetic variability. Only the traits canopy diameter and fruit ripening time showed significant block effects ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the trait canopy diameter, the genotypic effects were significant ( Table 4 ), indicating the existence of genetic variability among clones. Mistro et al [ 20 ], evaluating conilon coffee progenies for yield per plant, also found genetic variability. Only the traits canopy diameter and fruit ripening time showed significant block effects ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the traits fruit ripening time and fruit size, the individual broad-sense heritability estimates were of moderate magnitude (0.15<h 2 <0.50) ( Table 5 ). Mistro et al [ 20 ], evaluating progenies of conilon coffee regarding yield per plant, obtained a moderate magnitude heritability estimate.…”
Section: Resultsmentioning
confidence: 99%
“…In this view, vegetative propagation is the most common practice, ensuring uniform crop development, high yields, better coffee quality and better maturation patterns [7][8][9], although it reduces the species genetic diversity. Therefore, exploring the genetic diversity in coffee farms is of utmost importance to achieve crop sustainability [10,11]. Several studies have addressed this topic in order to identify elite genotypes of C. canephora [9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have investigated the response of C. canephora in colder regions of Brazil, according to the latitude or altitude (Mistro et al 2004, Barbosa et al 2014, Silva et al 2015, Mistro et al 2019, but none of the efforts culminated in the registration of a cultivar with high yielding potential, as in the case of Andina.…”
Section: Introductionmentioning
confidence: 99%